Global Single-Cell Sequencing Landscape of Adipose Tissue of Different Anatomical Site Origin in Humans - Shixing Gu; Zhenyu Gong; Shuncai Liu; Guohao Lu; Yu Ling; Yanlin Wei; Ting Li; Ronghe Gu; Yongxian Rong; Junjun Li; Hongmian Li (Stem Cells International)
Chronic refractory wounds (CRW) are one of the most serious clinical challenges for surgeons to address. Stromal vascular fraction gels (SVFG), including human adipose stem cells (hASCs), have excellent vascular regenerative and tissue repair properties. Here, we combined single-cell RNA sequencing (scRNA-seq) of leg subcutaneous adipose tissue samples with scRNA-seq data from abdominal subcutaneous adipose tissue, leg subcutaneous adipose tissue, and visceral adipose tissue samples from public databases. The results showed specific differences in cellular levels in adipose tissue from different anatomical site sources. We identified cells including CD4+ T cells, hASCs, adipocyte (APC), epithelial (Ep) cells, and preadipocyte. In particular, the dynamics between groups of hASCs, epithelial cells, APCs, and precursor cells in adipose tissue of different anatomical site origins were more significant. Furthermore, our analysis reveals alterations at the cellular level and molecular level, as well as the biological signaling pathways involved in these subpopulations of cells with specific alterations. In particular, certain subpopulations of hASCs have higher cell stemness, which may be related to lipogenic differentiation capacity and may be beneficial in promoting CRW treatment and healing. In general, our study captures a human single-cell transcriptome profile across adipose depots, the cell type identification and analysis of which may help dissect the function and role of cells with specific alterations present in adipose tissue and may provide new ideas and approaches for the treatment of CRW in the clinical setting.